2001
DOI: 10.1103/physrevb.63.075102
|View full text |Cite
|
Sign up to set email alerts
|

Spin-charge separation in the single-hole-doped Mott antiferromagnet

Abstract: The motion of a single hole in a Mott antiferromagnet is investigated based on the t − J model. An exact expression of the energy spectrum is obtained, in which the irreparable phase string effect [Phys. Rev. Lett. 77, 5102 (1996)] is explicitly present. By identifying the phase string effect with spin backflow, we point out that spin-charge separation must exist in such a system: the doped hole has to decay into a neutral spinon and a spinless holon, together with the phase string. We show that while the spin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(62 citation statements)
references
References 34 publications
4
58
0
Order By: Relevance
“…In the latter case, the doped hole is found to have finite spectral weight and a coherent dispersion with the bandwidth comparable to J. The discrepancy may arise from the small sample sizes in exact diagonalization calculations: The phase string effect, which leads to the mutual Chern-Simons gauge fields, starts to play the role of self-localization only when the sample sizes become larger than the localization length scales 46 . Further investigations from both analytic and numerical approaches to clarify this issue are needed.…”
Section: Low Dopingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the latter case, the doped hole is found to have finite spectral weight and a coherent dispersion with the bandwidth comparable to J. The discrepancy may arise from the small sample sizes in exact diagonalization calculations: The phase string effect, which leads to the mutual Chern-Simons gauge fields, starts to play the role of self-localization only when the sample sizes become larger than the localization length scales 46 . Further investigations from both analytic and numerical approaches to clarify this issue are needed.…”
Section: Low Dopingmentioning
confidence: 99%
“…Therefore, the external magnetic flux is not allowed to present in the bulk (i.e., the Meissner effect) unless it is quantized in multiples of half flux quanta given in (46). In particular, for a magnetic flux quantized at the minimal half flux quantum Φ e min , there must be a spinon trapped near the vortex core according to (45) by noting that the "charge" 2N vor of the vortices produced by holon field is always in units of 2π (i.e., Φ 0 ).…”
Section: B Meissner Effect and Spinon Confinement In Sc Phasementioning
confidence: 99%
“…These give rise to interference effects which are very different from the ones familiar from simple quantum mechanics, since they are inherently tied to the quantum many-body nature of the spin system. It was recently [19] demonstrated that this goes so far that even in the perfect translationally invariant case the hole is subjected to self-localization [20]. In section IV we will unveil the nature of the mechanism leading to this self-localization, resting on a general path-integral consideration and a mean-field like approximation.…”
Section: Fig 2 (Color Online) (A)mentioning
confidence: 99%
“…We add that there are also efforts to bosonize the t-J model, [13] but digging out the fermionic excitations turns out to be difficult, except possibly for the one-hole problem. [14] Recently, a new representation of the t-J model in terms of two-band fermions was proposed. [15] The idea is to let one of the band, say the p-fermion band, to carry the spin and charge of doped particles, while the other singly-occupied half-filled band, say the f -fermion band, to reflect the neutral spin background.…”
mentioning
confidence: 99%